Factors in job characteristics influence employee's motivation in the Mara State Office of Melaka / Ruzlina Hussain - Hussain, Ruzlina (Faculty of Business and Management, 2013)
Motivation was a set of courses concerned with a kid of strength that boosts performance and directs towards accomplishing certain targets ( Talimullah et aI, 2010; Quratul-Ain, 2011). Employees' individual performance has a significant impact on the organizational performance. Therefore, managers always try to find ways to stimulate their employees' work motivation (Wood et aI., 1994; Fang Yang, 2011). This is supported by Rutherford (1990) in Quratul-Ain (2011) reported that motivation formulates an organization more successful because motivated employees are constantly looking for improved practices to do a work, so it was essential for organizations to encourage motivation of their employees (Kalimullah, 2010; QuratulAin, 2011). In order to help managers to effectively motivate their employees, a large amount of research has been conducted to identify the factors which can motivate employees. Therefore, Ross (1998) in Fang Yang (2011) stated that several versions of a motivation theory were generated in the nineteenth century and Job Design Theory proposed by Hackman and Oldham in 1980 was used in this research. This theory supposes that the task itself, which refers to internal factors, was a key to employee' s work motivation (Ramlall, 2004; Fang Yang, 2011). It reports that the employees can be motivated through five job characteristics; skill variety, task identity, task significance, autonomy and feedback.